SmBa1-xCaxCo2O5+d Layered Perovskite Cathodes for Intermediate Temperature-operating Solid Oxide Fuel Cells - Song, Kyeong Eun; Woo, Sung Hun; Baek, Seung Wook; Kang, Hyunil; Choi, Won Seok; Park, Jun Young; Kim, Jung Hyun (Frontiers in Chemistry, 2021)
In SmBa1-xCaxCo2O5+d (x=0.01, 0.03, 0.1, and 0.2, SBCCO) oxide systems calcined at 1100 oC for 8 hours, the XRD patterns of the SBCCO single phase were maintained in the cases of SmBa0.97Ca0.03Co2O5+d (SBCCO-0.97) and SmBa0.99Ca0.01Co2O5+d (SBCCO-0.99) compositions. In SmBa0.8Ca0.2Co2O5+d (SBCCO-0.8) and SmBa0.9Ca0.1Co2O5+d (SBCCO-0.9), CaCoSmO4 existed with the pattern SBCCO. SBCCO structures were identified as orthorhombic crystal structures because they showed splitting of the X-ray diffraction (XRD) peaks at 23.4o, 47.9o, and 59.1o. Typical metallic conduction behaviors were found in all measured compositions except SBCCO-0.8, which showed a metal-insulator transition (MIT) behavior. Compared to other SmBa1-xCaxCo2O5+d compositions, SBCCO-0.8 showed the highest electrical conductivity of 460 S/cm at 500 oC. In particular, SBCCO-0.9 was found to have an excellent ASR characteristic of about 0.077 Ωcm2 at 700 oC. The activation energy of SBCCO-0.9 was the lowest among SBCCO oxide systems with a value of 0.77 eV.